Perancangan User Experience dengan menggunakan Metode HCD dan UEQ (Studi Kasus: Layanan Peminjaman Asset Biro Umum dan Protokol Setda Provinsi Bali) - Luh Putu Dessy Citra Yoseva Wardana; Satrio Hadi Wijoyo; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Biro Umum dan Protokol Setda Provinsi Bali has asets that can be borrowed, namely buildings, meeting rooms and four-wheeled vehicles. The loan process is currently still done manually, where the borrower must visit directly to Biro Umum dan Protokol Setda Provinsi Bali by bringing a loan license and meet Kepala Biro as manager to get loan approval. The absence of information about the loan schedule information and the availability of asets that can be borrowed, making borrowers sometimes apply for dates that have been ordered by other borrowers. The purpose of this research is to design user experience information system for lending services using the HCD method and adopting the UEQ aspect of the design process. The design process must pay attention to the user experience such as attractiveness, dependability, efficiency, novelty, perspicuity and stimulation so that the user experience achieved is good and supports in the process of identifying user needs in the Human Centered Design method. The resulting design is a prototype website and will be tested using the User Experience Questionnaire (UEQ). UEQ test results have a positive category mean and six UEQ scales are in the excellent category.